Establishing the female voice in contemporary Nigerian narrative through Nego-Feninism: a study of Abubakar Gimba's Sacred Apples - Muhammad, Nasiru Umar; Talif, Rosli; Jujar Singh, Hardev Kaur; Bahar, Ida Baizura (Universiti Putra Malaysia Press, 2016)
In African Male Writings, as in other writings from the other regions of the world, the tradition of domination of women has been long established-a patriarchal (mis) adventure. This is partly because for a very long time, male authors have dominated the writing and criticism of African Literature which gives birth to the present state of affairs. Nego-Feminism is a relatively new theory which confronts the issues of patriarchy and female dominance through negotiation and non-confrontational attitudes in dealing with the feminist struggles that occur on the continent. It considers the implications of patriarchal traditions and customs and aims to dismantle them and negotiate for a better position through the power of the pen in the literary discourse. This article seeks to interrogate this exercise of negotiation in the contemporary African Novel in relation to the female voice as given to women by male writers to express their non-confrontational stand in the contemporary male authors narrative from Northern Nigeria using Abubakar Gimba’s Sacred Apples as an example.